Falling for the forbidden duke - Shepherd, Eva (Harlequin historicals., 2023)
"Illegitimate Georgina Daglish is used to staying in the shadows and letting her half sister, Olivia, shine. So when they arrive at the stately home of Luther Rosemont, the Duke of Southbridge, in the hopes of a proposal for Olivia, Georgina keeps to the wings. But when Olivia falls ill, Georgina's forced to entertain the devilish duke, and their time spent together sparks an undeniable--and completely off-limits--desire!"--Back cover.